2015
DOI: 10.1536/ihj.14-162
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Right Ventricular Basal Free Wall Strain by Two-Dimensional Speckle Tracking Echocardiography in Patients With Chronic Thromboembolic Pulmonary Hypertension

Abstract: SummaryRecently two-dimensional (2D) speckle tracking echocardiography (STE) derived from right ventricular (RV) free wall has been shown to be a very useful tool for the estimation of RV performance. The purpose of this study was to examine whether RV basal free wall strain can detect increased mean pulmonary arterial pressure (mPAP) in patients with chronic thromboembolic pulmonary hypertension (CTEPH). We investigated a total of 126 patients with CTEPH (mean age, 56 ± 12 years). They underwent echocardiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…An elevated mean pulmonary arterial pressure (mPAP) (> 30 mmHg) is reported to have a poor prognosis. 1,2) Recently, the CHEST-1 study demonstrated the improvement of exercise tolerance by administration of riociguat, a soluble guanylate cyclase stimulator, 3) but there was insufficient reduction of mPAP. Although pulmonary endoaterectomy (PEA) is a first choice for treatment of CTEPH, 4) not all patients are suitable candidates due to distal localization of the lesions or to the high risk associated with surgery.…”
mentioning
confidence: 99%
“…An elevated mean pulmonary arterial pressure (mPAP) (> 30 mmHg) is reported to have a poor prognosis. 1,2) Recently, the CHEST-1 study demonstrated the improvement of exercise tolerance by administration of riociguat, a soluble guanylate cyclase stimulator, 3) but there was insufficient reduction of mPAP. Although pulmonary endoaterectomy (PEA) is a first choice for treatment of CTEPH, 4) not all patients are suitable candidates due to distal localization of the lesions or to the high risk associated with surgery.…”
mentioning
confidence: 99%
“…The median RV end diastolic diameter was reduced from 41 (36-52) mm to 34 (29-41) mm (P = 0.005). The Qanadli score was significantly reduced from 19 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) to 11 (3-15) (P = 0.005).…”
Section: Resultsmentioning
confidence: 95%
“…All patients had a symptom duration of less than 14 days and were at intermediate risk (normotensive, RV dysfunction or dilatation). On CT, PE with a median Qanadli score of 19 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) USAT IN SUBMASSIVE PULMONARY EMBOLISM was 34 (22-50) mmHg during catheterization. USAT were performed successfully in all patients.…”
Section: Resultsmentioning
confidence: 99%
“…Polanowski, et al 28) showed that dynamic coupling between the RV and pulmonary arteries is more disturbed in CTEPH than in PAH, despite similar levels of PAP. This may cause RV strain, 29) resulting in T wave inversion in the precordial leads. However, the reason is uncertain.…”
Section: )mentioning
confidence: 99%